Applications of logic of correlated knowledge to quantum mechanics - Giedra, Haroldas; Alonderis, Romas (Lietuvos matematikos rinkinys, 2018)
Knowledge of agents associated to particles of quantum system has been modelled in the paper. Also analysis of formulas and satisfiability in the model have been done.
Keywords: logic of correlated knowledge; quantum system; agent